If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2x = x + 26 Reorder the terms: 2x = 26 + x Solving 2x = 26 + x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-1x' to each side of the equation. 2x + -1x = 26 + x + -1x Combine like terms: 2x + -1x = 1x 1x = 26 + x + -1x Combine like terms: x + -1x = 0 1x = 26 + 0 1x = 26 Divide each side by '1'. x = 26 Simplifying x = 26
| 4r^2-18r-100=0 | | x+(2x)=12xy*y^2 | | -5(t-3)-(t+4)=10 | | A=2(L+W)(W) | | A=2(L+W) | | 21+(-47)+12+38+(-54)= | | 6y-12y+3= | | X^4-5x^3+11x^2-25x+30=0 | | c=gm | | (2x-3y)(x+2y)=0 | | 6y+12y+3= | | X-5=(2x-3) | | 25r^3-9r=0 | | 8x+9=4x-5 | | 4x+5=6x | | 3y+4z=16(y+z) | | 6v^2-3v+1=0 | | X-5=2(3-x) | | (4x-8)-(7x+9)= | | x-4y=u | | 5=4m+4u | | 7x-35+14=7 | | (4/5)1.175= | | 3x-(5x-4)= | | 3p^4-18p^3-81p^2= | | 1+x-2x+3x-4x=0 | | 3x-4=2(X+5) | | .8x-.6x+.3x=3 | | 7x+8y+3=0 | | 3(a+b)-2(a-b)=0 | | (x)2.75x+71.48= | | -5(t-6)-(t+9)=2 |